Présentation du dossier - Claude Gautier; Emmanuel Renault (Astérion)
In light of heated recent debates about neutrality and scientificity in social sciences, this issue seizes the opportunity to reconsider the terms of epistemological and political arguments concerning the relationships between critique and social sciences.